Air‐Stable, Efficient Mixed‐Cation Perovskite Solar Cells with Cu Electrode by Scalable Fabrication of Active Layer. Issue 11 (4th April 2016) - Deng, Yehao; Dong, Qingfeng; Bi, Cheng; Yuan, Yongbo; Huang, Jinsong
Abstract : High efficiency and air stable doctor‐blade coated perovskite solar cells are reported . The high quality mixed cation perovskite film (FA x MA1− x PbI3 ) is fabricated by taking the unique advantage of doctor‐blade coating method, based on which solar cell efficiency larger than 18% is realized. In addition, choosing copper as cathode enhances device environmental stability substantially, paving the way for real applications.